Effects of tobacco smoking on pulmonary function indices among undergraduate students (Nigerian Journal of Medical Rehabilitation, 2015)
Background: Tobacco smoking is a risk factor for chronic respiratory disorders. The tobacco epidemic is driven by adolescents and young adults. Tobacco-related morbidity rises with increasing years of smoking, and the increasing number of young smokers may have considerable future public health implications.Objective: This study investigated the effect of tobacco smoking on pulmonary function indices among undergraduate students. Methods: This is a cross sectional study involving 104 male undergraduate students between 18 and 30 years of age. They were recruited by snowball sampling and were grouped based on their smoking status (current smoker 52: non-smoker 52). Participants with signs of respiratory disease, thoracic spine deformity, or contraindication to spirometry were excluded from the study. Participants’ forced vital capacity (FVC), forced expiratory volume in first second (FEV1), both in litres, and forced expiratory ratio (FER) in percentage were assessed using standard protocols. Data were analyzed using mean, standard deviation, independent t-test and chi-square test with alpha level set at 0.05.Results: The two groups were not significantly different in age, height and body mass index (BMI). Smokers had significantly reduced FVC (3.42±0.42 vs 3.87±0.4 litres) p=0.03; FEV1 (2.39±0.37 vs 3.22±0.38 litres) p=0.001 and FER (%) (70.7±7.58vs82.3±4.05) p=0.01. Among the smokers, a relationship was observed between years and numbers of cigarettes smoked and lung function. The proportion of participants with FER below the age-matched reference was significantly higher among smokers than non-smokers (40.4%vs6.7%) at p=0.021. Conclusion: Smoking reduced pulmonary function among undergraduate students. This may have important public health implications since continued smoking may accelerate lung function deterioration and consequently increase the future risk of developing lung disease.